Psychological Mechanisms of the Influence of Empathic Characteristics on Adolescent Aggression - Burteshova A.B. (Euro Asian Journal Publishing, 2023)
The author defines such concepts as aggression and empathy, considers development of the empathic abilities in juvenile age, and its correlation with the aggression. The author carries out a research aimed to reveal special features of the adolescent aggression according to the different empathy levels.
Keywords: aggression; aggressive behavior; empathy; adolescence